Increased breast cancer cell toxicity by palladination of the polyamine analogue N1,N11-bis(ethyl)norspermine - Silva, Tânia M. (2014)
Breast cancer is one of the most common malignant tumor forms among women and many women succumb to their disease. Thus, new anticancer agents that can efficiently improve patient survival are of the utmost importance. In this study, the effects of the polyamine analogues N1,N11-bis(ethyl)norspermine (BENSpm) and N1-cyclo-propylmethyl-N11-ethylnorspermine (CPENSpm) and the synthesized dinuclear complexes Pd2BENSpm (Pd- BENSpm), Pt2CPENSpm (Pt-CPENSpm) and Pd2Spm (Pd- Spm) were investigated in normal-like breast epithelial MCF-10A cells and the breast cancer cell lines JIMT-1 and L56BR-C1. The overall data show that palladination of BENSpm resulted in enhanced cytotoxicity, in contrast to platination of CPENSpm that reduced cytotoxicity, which might be explained by differences in the cellular uptake of Pd-BENSpm and Pt-CPENSpm. BENSpm and Pd-BENSpm treatment reduced the CD44?CD24- putative cancer stem cell population, evaluated by flow cytometry. Furthermore, Pd-BENSpm was the most efficient compound regarding induction of DNA damage and decrease in colony formation in soft agar. Pt-CPENSpm and Pd-Spm, on the other hand, were shown to be the least toxic compounds of all tested. Pd-Spm efficiently reduced the cellular glutathione levels, which probably was a consequence of its metabolic inactivation by conjugation to this endogenous thiol. The normal-like cells were found to be less sensitive to the agents than the breast cancer cells. Our findings show that Pd-BENSpm exhibits promising anticancer effects which render it suitable for further optimization to develop a new metal-based chemotherapeutic drug for breast cancer treatment.